2021
DOI: 10.1186/s13550-021-00867-7
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid PET quantification using low-dose CT-guided anatomic standardization

Abstract: Background Centiloid (CL) scaling has become a standardized quantitative measure in amyloid PET because it facilitates the direct comparison of results across institutions, even when different analytical methods or tracers are used. Standard volumes of interest must be used to calculate the CL scale after the anatomic standardization of amyloid PET images using coregistered MRI; if the MRI is unavailable, the CL scale cannot be accurately calculated. This study sought to determine the substitut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…The prediction accuracy was significantly higher in the YC than the AD group (p < 0.05). The reported cut-off for the Centiloid scale for normal cognition and AD is 10-35 [6,[30][31][32][33]. The present findings showed that the respective Centiloid ranges for YC and AD were −18.26-28.7 and −22.2-160.7.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…The prediction accuracy was significantly higher in the YC than the AD group (p < 0.05). The reported cut-off for the Centiloid scale for normal cognition and AD is 10-35 [6,[30][31][32][33]. The present findings showed that the respective Centiloid ranges for YC and AD were −18.26-28.7 and −22.2-160.7.…”
Section: Discussionmentioning
confidence: 45%
“…It involves co-registration of the PET and MRI images of the same subject, anatomical standardization, VOI analysis using specific VOIs, and the conversion process from SUVR to the Centiloid scale. To overcome this, a simple method of calculating the Centiloid scale using low-dose CT instead of MRI has been reported [5][6][7]. However, manual image analysis and acquisition of anatomical images are still required, and no studies have been reported that automatically calculate the Centiloid scale using only PET images.…”
Section: Introductionmentioning
confidence: 99%
“…Although MRI is used to anatomically standardize PET for the calculation of the CL scale, another study purpose was to determine whether low-dose CT for attenuation correction used in PET/CT equipment can be a substitute for MRI. We have already confirmed the substitutability of low-dose CT in the calculation of the CL scale with 18 F-flutemetamol PET (Matsuda et al, 2021) and, in this study, we examine its application to 18 F-florbetapir.…”
Section: Introductionmentioning
confidence: 56%
“…Previous studies have examined the use of low‐dose CT of PET/CT equipment as a substitute for MRI in the calculation of the CL scale (Kim et al., 2022 ; Matsuda et al., 2021 ; Presotto et al., 2018 ). Our study using 18 F‐flutemetamol revealed that low‐dose CT provided a CL scale comparable to that of MRI.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, substantial progress has been made in calculating CL values and/or SUVR from amyloid PET images. Some of these methods use computed tomography (CT) instead of magnetic resonance imaging (MRI) for anatomical reference because they are more readily available [ 6 , 7 ]. Additionally, some methods do not require MRI or CT anatomical assistance, allowing automated analysis of amyloid PET images while optimizing accurate spatial normalization [ 8 ].…”
Section: Introductionmentioning
confidence: 99%